Conjugate addition/cyclization of propanal with isatylidene malononitriles: an efficient one-pot organocatalytic approach for the synthesis of 3′-methyl spiro[2H-pyran-3,4′-indoline] - Patil, Baliram R.; Nichinde, Chandrakant B.; Girase, Amardipsing S.; Chaudhari, Suryakant S.; Kinage, Anil K. (Organic & Biomolecular Chemistry, 2025)
The organocatalyzed one-pot Michael addition reaction of propanal to isatylidene malononitriles remains largely unexplored due to challenges in controlling the reaction and preventing side processes such as aldol condensation, self-aldolization, and 1,3-dipolar cycloaddition. In this study, we introduce a one-pot methodology for the synthesis of 3 `-alkyl spiro[2H-pyran-3,4 `-indoline] via an organocatalyzed Michael addition of simple propanal to isatylidene malononitrile derivatives, which are generated in situ from isatin derivatives and malononitrile. Subsequent reduction of the Michael adduct with NaBH4 leads to the target product with high efficiency under mild conditions. This strategy offers several advantages, including environmental sustainability, high to excellent yields, shorter reaction times, cost-effectiveness, and ease of implementation.